APPLYING ARTIFICIAL INTELLIGENCE TO IMPROVE SAFETY AND THE MICROGRID CONTROLLING SYSTEM - Mamadaliyev , Musulmonkul Imomali ugli; Abdusalyamova , Tillokhon (Educational Research in Universal Sciences, 2023)
Microgrids, a newer form of power grid architecture, are gaining popularity among researchers and enterprises. The ability to integrate renewable generation, electric vehicles (EV), energy storage, and distributed energy resources into the power grid and connect them with effective communication links gives a potential to increase power grid efficiency.